(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The article covers the importance and factors of strategies in the management of entrepreneurial activity, the content of management strategies. Problems in the development and formation of management strategies and are indicated. Also, in the economy of the Namangan region, economic indicators and analysis of the results of the strategy implemented in entrepreneurial activity are presented; recommendations for solving existing problems are developed.